High peak power pulses from dispersion optimised modelocked semiconductor laser. Issue 13 (1st June 2013) - Balzer, J.C.; Schlauch, T.; Klehr, A.; Erbert, G.; Tränkle, G.; Hofmann, M.R.
Abstract : Presented is an electrically pumped passively modelocked edge‐emitting semiconductor laser system in an external cavity setup with intracavity dispersion management. This concept, in combination with a pulse compressor, provides pulses as short as 158 fs. By expanding the setup with a tapered diode laser amplifier, peak powers up to 6.5 kW were achieved in the 850 nm wavelength range.